SORGHUM AS AN BIOENERGY AND FOOD SELF-SUFFICIENCY - Khaidir; Usnawiyah; Hendrival; Hafifah; Elvira Sari Dewi; Muhammad Yusuf N; Zurrahmi Wirda (Global Science Society, 2021)
ABSTRACT Sorghum is a food crop commodity that has important potential as a source of food and renewable energy for food and energy independence during the COVID-19 pandemic. Community service activities regarding processing sorghum into food and energy are very important in dealing with food dependence on rice and fuel energy from crude oil. Through extension activities and training on sorghum processing, it is hoped that it can increase public knowledge about sorghum and its processing. The method used is counseling and training on sorghum processing to the community. Extension and training activities for processing sorghum into alternative food and renewable energy in order to increase community knowledge in Blang Nibong Village, Samudera District, North Aceh Regency have been carried out and can be well received by the community. The community is very enthusiastic about participating in the service activities. The community has knowledge of the processing of sorghum into sorghum flour as an ingredient for processed food products such as steamed brownies, krispi tofu spices, cakes, and nagasari. Partners also have knowledge about other benefits of sorghum, namely as a renewable energy source. Sorghum stalks are known to contain bioethanol as fuel. Programs like this are very important to carry out, especially for people living in rural areas that have the potential for developing sorghum areas so that the program will be sustainable.